Effectiveness of Porous Durian Shell-based Activated Carbon for Methylene Blue Adsorption - Suriani binti Abu Bakar, Azmi bin Mohamed, Azlan bin Kamari, Muhammad Noorazlan Bin Abd Azis, Norhayati binti Hashim (Tanjung Malim, 2024)
Effectiveness of Porous Durian Shell-based Activated Carbon for Methylene Blue Adsorption by Suriani binti Abu Bakar, Azmi bin Mohamed, Azlan bin Kamari, Muhammad Noorazlan Bin Abd Azis, Norhayati binti Hashim